An Industrial systems study on BestFeet Manufacturing Corporation - Cruz, Rommel; Fernandez, Glenn; Javier, Harold; Santos, Allan T. (College of Engineering, 2002)
The group conducted an Industrial Systems Study on BestFeet Manufacturing Corporation (BFMC), a company that manufactures shoes and specializes in the production of hot-weathered boots. Specifically, the study focuses on the following concerns: corporate, business, and functional strategies that the company can pursue towards growth and development. Recommendations include strategies on market expansion that focuses on certain market segments, specifically the AFP and PNP. These areas of interests are thoroughly analyzed with the aim of finding related problems and providing solutions for improvement. With the use of the Seven S Model, the present system of BFMC is documented in terms of its structure, style, system, skills, strategy, staff and super-ordinate goals. After documenting the current system, the company's strengths and weaknesses, together with the opportunities and threats are assessed by conducting SWOT analysis. Here, external and internal factors that affect and might affect the company are evaluated. Based on the results of the SWOT analysis, strategies are developed. These strategies are then planned for implementation on short to long-term basis. The main problems identified by the group are: unreliable forecasting, insufficient capacity and low production line efficiency. The group then suggested strategies that will be useful in overcoming the problems identified. For the first problem, the marketing department should get acquainted with the proposed method of forecasting. It is imperative that sales data are always filed for they are the primary input to the method. The company can use the AB:POM software to facilitate the task of forecasting. The company should evaluate the performance of the chosen method to determine whether it remains responsive to existing internal and external conditions. For the second problem, in addition to the scheduling of the manpower, which would fill in for much-required overtimes, implementation of alternatives would involve purchasing of the required machineries way before the projected shortage in capacity. As an example, for the pre-fitting workstation, the additional machine may be purchased at anytime before the year 2004 when the shortage in labor hours can no longer be covered by overtime. Overtime requirements will be implemented not later than the end of the first half of the year in order to avoid stockouts. For the third problem, a possible solution would be to balance the production line by grouping certain operations in workstations. To further increase the capacity of the system, the company may opt to drop the casual shoes segment since they only comprise about 14% of the total production volume. Also, this segment is serving an already saturated market. Eliminating the casual shoes product line will lighten the load of each workstation. As a whole, production efficiency can be expected to increase by 75%. For further study, the group suggests an investigation into the feasibility of doing life cycle assessment of hot-weather combat boots and the possibility of BFMC in acquiring an ISO 14000 certification. Both inquiries would be beneficial to the company and would contribute to the protection of the environment.